KEPASTIAN HUKUM AKTA PERJANJIAN TERKAIT PINJAM NAMA (NOMINEE) OLEH WARGA NEGARA ASING (WNA) DALAM JUAL BELI TANAH MENURUT UNDANGUNDANG POKOK AGRARIA. - Irawan, Wendy; Nasseri, Jelly; Marniati, Felicitas Sri (SENTRI: Jurnal Riset Ilmiah, 2024)
Nominee agreements in buying and selling freehold land are prohibited according to applicable law. The phenomenon that occurs in society is that nominee agreements are still used by foreign citizens in buying and selling land. The formulation of the problem in this research is the legal consequences of a deed of agreement to borrow a name in the sale and purchase of land by a foreign citizen and what is the legal certainty of the deed of agreement regarding the borrowing of a name (nominee) by a foreign citizen (WNA) in the sale and purchase of land according to the Basic Agrarian Law. The legal theory used in this research is the theory of legal certainty by Jan Michiel Otto, the theory of legal consequences according to Soeroso. The method used in this research is a type of normative juridical research, namely legal library research or secondary and tertiary sources of legal materials. The research approaches used are the statutory approach, conceptual approach, case approach and analytical approach, and legal material collection techniques are carried out by identifying ang inventorying positive legal rules, book literature, journals and order sources of legal material. The analysis out using legal interpretation, including Grammatical Interpretation and Historical Interpretation ang analogy legal construction methods. From the results results can be obtained that the the legal implication on the nominee agreement to the land agreement by WNA are null and void because it does not meet the requirements to the Article 1320 Number 4 of the KUH Perdata and conflicted with the principle of Nationalism as emphasized in Article 26 Paragraph (2) UUPA so that parties related to the land agreement based on a nominee agreement shall be subject to civil liability. The legal certainty about the nominee agreement by the WNA to the land agreement based on the UUPA is carried out in a preventive manner by establishing statutory regulations that prohibit nominee agreements in relation to land rights so as to protect foreign nationals from possible losses and fraud that could threaten the security of foreign investment in Indonesia